PENGENDALIAN BANJIR DAN SEDIMEN DENGAN PEMBERDAYAAN MASYARAKAT DI HULU SUNGAI CABODO, KABUPATEN BANTAENG - Yusuf, Andi Rumpang; Akrim, Djusdil; Yuniarto, Eko (JEBE: Journal of Environment Behavior and Engineering, 2024)
For decades, residents have lived along the Cabodo River. Especially residents who live in Kasiping Hamlet, Bonto Tiro Village, Sinoa District, Bantaeng Regency. Starting to tend to be pessimistic and resigned to the natural conditions faced. Thus the aim of this research is to increase the independence of community involvement in flood and sediment control in the upper reaches of the Cabodo River, Bantaeng Regency. This study used a qualitative-descriptive method, collecting research data using observation and documentation. The results of this study are expected to (1) Increase the understanding of residents regarding disaster mitigation; (2) Involvement of residents consciously and actively in the form of Community Empowerment (3) Utilization of locally available materials in abundance in nature as cliff reinforcement materials for flood and sediment control. in Kasiping Hamlet, Bonto Tiro Village, Sinoa District, Bantaeng Regency.